2015
DOI: 10.3892/mmr.2015.4738
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-200a mediates nasopharyngeal carcinoma cell proliferation through the activation of nuclear factor-κB

Abstract: In nasopharyngeal carcinoma (NPC), the nuclear factor-κB (NF-κB) signaling pathway is highly active. The constitutive activation of NF-κB prompts malignant cell proliferation, and microRNAs are considered an important mediator in regulating the NF-κB signaling pathway. The current study investigated the effect of microRNA-200a (miR-200a) on NF-κB activation. Reverse transcription-quantitative polymerase chain reaction was used to quantify the relative level of miR-200a in NPC tissue samples and CNE2 cells. An … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“… 130 However, a number of studies have suggested that the NFκB pathway may upregulate the expression of LCN2 to promote the development of many cancers. 131 , 132 Therefore, the NFκB pathway is diversified in different tumor cells, 133 , 134 and the complex anticancer mechanism of the NFκB pathway is still not clear. Further study is warranted.…”
Section: Roles Of Nfκb In Cancermentioning
confidence: 99%
“… 130 However, a number of studies have suggested that the NFκB pathway may upregulate the expression of LCN2 to promote the development of many cancers. 131 , 132 Therefore, the NFκB pathway is diversified in different tumor cells, 133 , 134 and the complex anticancer mechanism of the NFκB pathway is still not clear. Further study is warranted.…”
Section: Roles Of Nfκb In Cancermentioning
confidence: 99%
“…In addition, Shi et al (2016) revealed that miRNA-200a activates the NF-κB signaling pathway through targeting IκBα, which is a negative regulator of NF-kB. Their particular study was limited to nasopharyngeal carcinoma cells (Shi et al, 2016).…”
Section: Mirna-141 Regulates Age-related Stimuli (Inflammatory and Oxidative Stress)mentioning
confidence: 99%
“…In addition, Shi et al (2016) revealed that miRNA-200a activates the NF-κB signaling pathway through targeting IκBα, which is a negative regulator of NF-kB. Their particular study was limited to nasopharyngeal carcinoma cells (Shi et al, 2016). It has been previously reported that NF-kB transcription activity was elevated in a number of tissues with aging and that inhibition of NF-kB leads to a delayed age-related pathogenesis {Tilstra et al, 2012 }.…”
Section: Mirna-141 Regulates Age-related Stimuli (Inflammatory and Oxidative Stress)mentioning
confidence: 99%
“…MicroRNA-200a (miR-200a), a member of the miR-200 family, has been reported to be dysregulated and function as a tumor inhibitor in the pathogenesis of various cancers, such as pancreatic carcinoma11, renal cell carcinoma12, nasopharyngeal carcinoma13, breast cancer14, ovarian cancer15and so on, including HCC. However, the exact role and molecular mechanism of miR-200a in liver cancer have not been elucidated yet.…”
Section: Introductionmentioning
confidence: 99%